Report of Amblyomma parvitarsum infesting goats in Midwestern Argentina - Fantozzi, María Cecilia; Tarragona, Evelina Luisa; Dayenoff, Patricio Mario; Cuervo Bustamante, Pablo Fernando; Mera y Sierra, Roberto; Nava, Santiago (Elsevier, 2018)
Adult ticks were collected from goats on September 2012 in the locality of Trintrica (35° 17′ 19″ S - 68° 44′ 6″ W, 1430 m.a.s.l.), Mendoza, Argentina. The specimens were identified as seven females and three males of Amblyomma parvitarsum Neumann, 1901. This record represents the new occurrence of A. parvitarsum in the province of Mendoza, as well as the first report of the parasitism in goats along the geographical range of A. parvitarsum.